Knot of Henry Variation and the Effect on Plantar Flexion Strength. (January 2020) - Thomas, Danielle; Thordarson, David; Nelson, Trevor J.; Charlton, Timothy P.; Eberlein, Samuel; Metzger, Melodie F.
Background: The flexor hallucis longus (FHL) and flexor digitorum longus (FDL) tendons are commonly used for tendon transfer in reconstructive foot and ankle procedures. Some patients experience great toe weakness and loss of push-off strength. The objective of this biomechanical study was to quantify plantarflexion force after FHL and FDL harvest and correlate it to variations in tendon crossover patterns at the knot of Henry to determine if specific patterns have an increased tendency toward forefoot weakness. Methods: Simulated loads through the Achilles, FHL, and FDL were applied to cadaveric specimens while plantarflexion force was measured using a pressure mapping system. Force was recorded with the FDL and FHL unloaded to simulate tendon transfer. Afterward, specimens were dissected to classify the tendinous slips between the FHL and FDL based on a previously determined system. Functional and anatomical relationships between the classification type and loading patterns were analyzed. Results: There were no statistical differences between the tendon crossover patterns in forefoot force reduction after FHL or FDL harvest. Average decrease in great toe and total forefoot pressure after FHL harvest was 31% and 22%, respectively. Average decrease in lesser toe and total forefoot push-off force after FDL harvest was 23% and 9%, respectively. Conclusion: This study quantified loss of plantarflexion force after simulated FHL and FDL harvest and correlated these losses to variations in anatomic crossover patterns at the knot of Henry. Variations at the knot of Henry do not contribute to differences in forefoot weakness. Clinical Relevance: The decrease in forefoot pressure seen here would help explain the clinical scenario where a patient does note a loss of great toe strength after FHL transfer.